2005
DOI: 10.1021/om050024k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Primary Carbon−Hydrogen Bonds of Alkanes by Carbene Insertion with a Silver-Based Catalyst

Abstract: The complexes [Tp Br3 Ag] 2 ‚CH 3 COCH 3 (1) and Tp Br3 Ag(thf) (2) catalyze the insertion of the :CHCO 2 Et group from ethyl diazoacetate (EDA) into the saturated C-H bonds of several C5, C6, and C8 linear and branched alkanes. In addition to secondary and/or tertiary sites, the unprecedented insertion into the primary C-H bonds of the substrates studied has been observed with variable regioselectivity, toward the methyl groups, within the range of 40-60% for branched and nearly 25% for linear alkanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 27 publications
4
71
1
Order By: Relevance
“…The metal carbenoids behave as very electrophilic species and the electron-withdrawing ester group reinforces the high reactivity, generating a system characterized by poor regioselectivity between different C-H bonds [27][28][29] . In recent years, extensive efforts have been made to attenuate the carbenoid reactivity by altering the nature of the catalysts, with some improvements having been made by using very bulky ligands with copper 30 and silver 31 complexes. The major breakthrough in this field, however, was the discovery that carbenoids functionalized with both donor and acceptor groups were much more chemoselective than the traditional carbenoids, as shown in Fig.…”
Section: C-h Functionalization By Metal Carbenoidsmentioning
confidence: 99%
“…The metal carbenoids behave as very electrophilic species and the electron-withdrawing ester group reinforces the high reactivity, generating a system characterized by poor regioselectivity between different C-H bonds [27][28][29] . In recent years, extensive efforts have been made to attenuate the carbenoid reactivity by altering the nature of the catalysts, with some improvements having been made by using very bulky ligands with copper 30 and silver 31 complexes. The major breakthrough in this field, however, was the discovery that carbenoids functionalized with both donor and acceptor groups were much more chemoselective than the traditional carbenoids, as shown in Fig.…”
Section: C-h Functionalization By Metal Carbenoidsmentioning
confidence: 99%
“…In 2005, Pérez and coworkers developed a highly active silver catalyst [Tp Br3 Ag] 2 (Me 2 CO) 2 for the transformation of sp 3 C-H bond of alkanes with carbene species (Scheme 3) [20]. Compared to silver catalyst 1, the substitution of ligand in silver catalysts 2 was changed from CF 3 (catalyst 1) to Br (catalyst 2) and showed higher efficiency of carbene insertion into sp 3 C-H bonds of various alkanes with EDA.…”
Section: Direct C-c Bond Formationmentioning
confidence: 99%
“…8.3), although no chemical yields were reported in either case. 20 The corresponding Cu-scorpionate complexes function well as cyclopropanation catalysts. 19,[21][22][23] Davies and Thompson have demonstrated that several donor-acceptor diazo compounds (35 and 37) participate in selective silver-catalyzed cyclopropanation of a variety of olefins with AgSbF 6 as catalyst at reflux in CH 2 Cl 2 (Schemes 8.6 and 8.7).…”
Section: Cyclopropanationmentioning
confidence: 99%